A fetal alcohol spectrum disorder diagnostic service and beyond: Outcomes for families. (October 2019) - Doak, Jessica; Katsikitis, Mary; Webster, Heidi; Wood, Andrew
Abstract: Background: Fetal alcohol spectrum disorder (FASD) is of significant concern for Australians for many reasons, one being Australia's drinking culture which increases the potential for FASD to occur. Aims: The current study aimed to explore the lived experiences of Australian caregivers who received a FASD diagnosis for a child in their care, using the Australian Guide to the Diagnosis of FASD . Methods and Procedures: Semi-structured interviews were conducted with seven caregivers whose children were assessed for FASD by a multidisciplinary team. Interviews explored how families experienced the FASD diagnostic process, and sought insight into outcomes for families following diagnosis, particularly in relation to accessing supports and services. Outcomes and Results: Through thematic analysis, five overarching themes were identified: (1) receiving a FASD diagnosis had a positive impact; (2) caregivers' evaluation of assessment process; (3) positive support services relative to FASD; (4) ongoing difficulties regardless of diagnosis; and (5) need for societal knowledge of FASD. Conclusions and Implications: Given the global need for standardised FASD diagnostic procedures and accurate reporting of prevalence rates, the current study provides a contribution to the emerging diagnostic FASD literature, and insight into families' experiences who have children diagnosed with FASD. What this paper adds: This study provides additional information to the developing pool of literature attempting to create a typical profile of FASD. Most importantly, this paper highlights the implementation of the Australian Guide to the Diagnosis of FASD, and evaluates caregivers' experiences of their child's FASD assessment process, within a public FASD diagnostic service, using the revised guidelines.